Psychometric properties of the Portuguese version of the Global Transformational Leadership (GTL) scale - van Beveren, Patrícia (2017)
The aim of this study is to adapt and consequently validate the Global Transformational Leadership mea-suring scale (GTL). The scale was therefore applied to a sample of 456 members of 70 work groups,belonging to 26 organizations. The factorial structure of the scale was analysed through the exploratoryfactor analysis (EFA) and confirmatory factor analysis (CFA), with the sample being split in two equalparts: EFA was conducted in both sub-samples and CFA was applied in the second sub-sample. The inter-nal consistency was evaluated via Cronbach’s alpha and the nomological validity was analysed via theevaluation of the GTL’s correlations with both team-level autonomy and quality of group experience.The results revealed the presence of a unidimensional scale with a good level of internal consistency.Regarding the nomological validity, the results pointed to hypothetical relations, since the GTL showedpositive correlations with the variables considered. Thus, the Portuguese version of the GTL is presentedas a useful instrument for evaluating transformational leadership.